Pollen-mediated gene flow across fragmented clonal stands of hybrid eucalypts in an exotic environment - da Silva, Paulo H.M.; Sebbenn, Alexandre M. [UNESP]; Grattapaglia, Dario (Elsevier, 2015)
We investigated the rate of pollen-mediated flow and realized reproductive success at increasing distances from the source, across fragmented clonal stands of hybrid eucalypts in Brazil by parentage analysis of grown out seedlings using genetic data at 15 microsatellite markers. Two study areas were employed: a pollen donor area composed of a clonal stand of a single pollen donor clone (PD) and a pollen sink (PS) area composed of a mixed clonal stand of two other clones (PS1 and PS2). In the pollen sink area four plots with 30 trees each, located at 25, 200, 400 and 550. m from the PD were established as sink islands. Before flowering, the entire clonal stands of clones PS1 and PS2, with exception of the sink islands were clear cut. Seeds were harvested from five randomly sampled trees in each sink island and the paternity of 15 seedlings per tree, 75 seedlings per island totaling a sample of 300 seedlings, was determined with PD as the alleged father. The self-pollination rate in the sink islands varied from zero to 24%. Paternity assignment to the PD was highest in the island at 25. m (17.3%) and rapidly decreased to 4.0% at 200. m and 2.7% at 550. m, suggesting a pattern of isolation by distance, while revealing a large pollen contribution from unaccounted sources across all islands. Our results in a fragmented clonal site agree with previous estimates of general pollen movement in eucalypt seed orchards, showing that pollination will take place by and large at relatively short distances of less than 200. m, consistent with the expected range of flight of pollinator bees. Nevertheless the exponential distribution observed also indicates that low levels of pollination success are to be expected over longer distances. Our data provide useful guidelines regarding the distance at which seed orchards should be established away from potentially large pollen pressure of clonal stands to minimize unwanted pollen introgression. Furthermore, our results on dispersal rate and distance of pollen have direct implications on gene containment strategies and modeling studies, as pollen-mediated gene flow is one of the key determinants of the potential ecological and biosafety impacts of prospective transgenic eucalypts.
Keywords: Eucalyptus; Outcrossing rate; Paternity analysis; Pollen flow; Transgenic tree